2009
DOI: 10.1111/j.1469-7610.2008.02001.x
|View full text |Cite
|
Sign up to set email alerts
|

Perception of tone and aspiration contrasts in Chinese children with dyslexia

Abstract: Dyslexia in non-alphabetic Chinese correlates with the categorical organization and accuracy of Cantonese speech perception, along the tone and aspiration dimensions. This association with reading is mediated by its association with phonological awareness. Therefore, dyslexia is universally at least partly a function of basic speech and phonological processes independent of whether the speech dimensions in question are coded in writing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 40 publications
3
52
0
Order By: Relevance
“…(Allophonic contrasts are variants on a given phoneme; e.g., in English, the /t/ sounds in time and subtle sound different when isolated, although they are both within the /t/ category.) This pattern of reduced accuracy and categorical perception for stop consonants has been found for Chinese children as well (e.g., Cheung et al 2008;Liu et al 2009). One prominent theory of such difficulties with stop consonant perceptions in children with dyslexia, termed the "temporal processing hypothesis" (Tallal 1980), is the idea that such difficulties might be due to deficient auditory perception of rapid transitional stimuli.…”
Section: The Role Of Auditory Sensitivity and Speech Perception In Rementioning
confidence: 85%
See 2 more Smart Citations
“…(Allophonic contrasts are variants on a given phoneme; e.g., in English, the /t/ sounds in time and subtle sound different when isolated, although they are both within the /t/ category.) This pattern of reduced accuracy and categorical perception for stop consonants has been found for Chinese children as well (e.g., Cheung et al 2008;Liu et al 2009). One prominent theory of such difficulties with stop consonant perceptions in children with dyslexia, termed the "temporal processing hypothesis" (Tallal 1980), is the idea that such difficulties might be due to deficient auditory perception of rapid transitional stimuli.…”
Section: The Role Of Auditory Sensitivity and Speech Perception In Rementioning
confidence: 85%
“…/fu1/ refers to 夫 (husband), and /fu2/, /fu3/, and /fu4/ each correspond to 浮 (float), 腐 (rot), and 富 (rich), respectively. Chinese (Cantonese-speaking) children with dyslexia (ages 8-10 years old) could be distinguished from those without dyslexia on lexical tone identification and categorical perception (e.g., Cheung et al 2008) in one study. In another study of those with and without a family history of dyslexia, 5-year-olds at risk for dyslexia were significantly poorer in distinguishing lexical tones (McBride-Chang, Lam et al 2008).…”
Section: The Role Of Auditory Sensitivity and Speech Perception In Rementioning
confidence: 99%
See 1 more Smart Citation
“…Turning to reading difficulties and developmental dyslexia, the majority of studies of Chinese children with developmental dyslexia have reported extensive deficits in phonological processing, encompassing phonological awareness, phonological memory and RAN (e.g., Chan & Siegel, 2001;Cheung et al, 2009;Ho & Lai, 1999;Ho & Ma, 1999;Ho, Law, & Ng, 2000;So & Siegel, 1997;Shu, Meng, Chen, Luan, & Cao, 2005). Some deficits in morphological awareness have also been reported (e.g., McBride-Chang et al, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…An extensive review of the related literature by Farmer and Klein (1995) has led to the hypothesis that developmental dyslexia is strongly linked to a general deficit in speed of processing (SOP) in both visual and auditory modalities. Chinese children with reading disorders have also been found to show poorer performance than chronological age matched (CA) children with normal reading abilities on visual and auditory temporal processing tasks, and a correlation between reading performance and orthographic processing (Cheung et al, 2009;Chung et al, 2008;Ho & Bryant, 1997;Ho, Chan, Lee, Tsang, & Luan, 2004;Liu, Shu, & Yang, 2009;Siok & Fletcher, 2001). Furthermore, it has been argued that morphological awareness is critical to reading development since Chinese characters represent morphemes, and poor morphological awareness is a core deficit underlying developmental dyslexia in Chinese (Wu, Packard, & Shu, 2009 for review).…”
Section: Introductionmentioning
confidence: 99%